Relation between Pesticide Exposure and Hypertension Incidence among Sprayers of Jasmine Farmers in Kaliprau Village, Ulujami District, Pemalang - Ali Wafa; Sulistiyani Sulistiyani; Tri Joko (Journal of Public Health for Tropical and Coastal Region, 2019)
Background: The use of pesticides in Kaliprau Village is not following the dosage required in the packaging label with the frequency of spraying 3-4 times per week. Spray farmers mix more than two types of pesticides and when spraying do not use personal protective equipment (PPE). The incidence of hypertension in Kaliprau Village in 2016 was 524 people and increased in 2017 to 843 people. The purpose of this study was to determine the relathionship between pesticide exposure and hypertension incidence among sprayers of jasmine farmer in Kaliprau Village, Ulujami District, Pemalang. Methods: This research is observational analytic using a survey method approach with cross-sectional design. The sample in this study was 102 respondents with data analysis using Chi-Square. Results: Data analysis shows that there is a relationship between years of work (p = 0,000). While the frequency of spraying (p = 0.574), spraying time (p = 0.739), length of work (p = 0.721), wind direction (p = 0.171), pesticide dose (p = 0.145), dilution method (p = 0.448), method storage (p = 0.648) not related to hypertension. Conclusions: there is a relationship between the length of service and the incidence of hypertension among sprayers of jasmine farmer in Kaliprau Village, Ulujami District, Pemalang District.